Penyuluhan bahaya riba di Mushola Al Hidayah Nguter Sukoharjo - Sumadi, Sumadi; Efendi, Tino Feri; Tho’in, Muhammad; Utami, Wikan Budi (Nur Science Institute, 2021)
The purpose of this service is to contribute to increasing the level of understanding of the people to provide knowledge to the community, especially in Islamic economic da'wah. This community service aims to advance understanding of sharia economics, especially regarding the dangers of usury. It is hoped that the results of this training will provide additional new understanding from the surrounding community. This activity uses the lecture method, discussion, simulation practice, and observation. The lecture method is used in the process of delivering training materials. The expected output targets of this activity are: 1) The community can know and understand the sharia economic system. 2) People get a new understanding of the dangers of usury. 3) Furthermore, the community will know and understand how to muamalah, transact in the development of a more Islamic and blessing life